Therapeutic politics and the institutionalisation of dignity: 'Treated like the Queen'. Issue 5 (September 2022) - Moran, Rebecca; Salter, Michael
This article draws on theories of therapeutic politics to explore the role of institutionalised dignity as a medium for the social and political participation of traumatised people. Using the Australian Royal Commission into Institutional Responses to Child Sexual Abuse as a case study, the article offers a psychosocial account of shame and humiliation as key characteristics of the phenomenology of trauma, and presents dignity as the organising principle of a therapeutic politics. Through interviews with survivors of child sexual abuse who testified to the Commission, as well as former Commission staff, the article describes the practices and structures of dignity as they were institutionalised within the Commission. We suggest that institutionalised dignity can ground and guide the theory and practice of a therapeutic politics and institutional responses to trauma, violence and abuse.